The Process of Dance Learning Based Sekolah.Id LMS at SMKN 1 Bandung - Wulan Purnamasari; Juju Masunah; beben Barnas (Universitas Pendidikan Indonesia, 2023)
The development of technology and information has now been applied in human life, including in the field of education. The presence of website-based technology is now being used as a medium or tool that can help teachers' performance in teaching and the learning process for students. This research aims to describe a comprehensive and integrated website to facilitate the teaching and learning process at SMKN 1 Bandung, especially in learning dance. The method used in this research is a descriptive analysis method with a qualitative approach. Data obtained from observations, interviews and documentation in the process of learning dance using the Sekolahan.id LMS is to find out the features and use of teachers and students at SMKN 1 Bandung. The results of this research show that the Sekolahan.id LMS in the process of learning dance at SMKN 1 Bandung has features that can help teachers in teaching and doing administration such as student absences, student data, creating final exam questions and others. LMS Sekolahan.id also makes it easier for students to learn. It is hoped that this research will also be an example for other schools, so that in the future there is no need to worry about whether the use of technology can be more optimal in helping learning at school.